ESTIMATION OF HETEROSIS IN FIELD CORN AND SWEET CORN AT MARKETABLE STAGE - KUMAR, RAJEEV; J. P. SHAHI; K. SRIVASTAVA (The Bioscan, 2013)
Heterosis of 40 crosses derived from a line × tester mating system involving eight sweet corn and five field corn inbreds were studied in both rabi (winter) and kharif (Rainy) season (2009-10). A total of 54 treatments comprising 13 parents (eight sweet corns and five field corns), their 40 crosses and one standard check (Madhuri sweet corn) were evaluated in a randomized block design with three replications. Each experimental plot has one 4 m row. The traits evaluated plant height, dehusked ear length, ear girth without husk, number of kernel per row, 100 kernel weights, marketable yield per hectare and total soluble solid at the time of fresh ear stage (marketable yield). The crosses DMSC4 × HUZM185, Dulce Amanillo × HUZM536, DMSC36 × HKI323 and Win Sweet Corn × HUZM 536 exhibited high positive significant heterosis over better parent and standard check for marketable yield and yield related traits as well as quality traits like, dehusked ear length, ear girth without husk, number of kernel per row, 100 kernel weight, and total soluble solid in winter and rainy season (2009-10). These crosses in future could be exploited commercially for higher yield and better quality in maize.